Clinical applications of PET and PET/CT in pediatric malignancies. Issue 5 (May 2010) - Kumar, Rakesh; Shandal, Varun; Shamim, Shamim Ahmed; Halanaik, Dhanapathi; Malhotra, Arun
The common childhood cancers are leukemia, CNS tumors, lymphomas, soft-tissue tumors (such as rhabdomyosarcoma and fibrosarcoma), neuroblastoma, malignant bone tumors, germ cell tumors with neoplasms of gonads and hepatic tumors. Usually the conventional imaging modalities, such as x-ray, ultrasound, computed tomography (CT) and MRI, are being routinely used for the management of these pediatric malignancies. However, most of these modalities provide structural information and are lacking in functional/metabolic status of these malignancies. Recently, PET and PET/CT have emerged as a functional diagnostic imaging modality for the management of various cancers in adult population. Up to now most of the data published in the literature are on PET alone. PET used in conjunction with CT is useful as it provides an enhanced view of the anatomical details and the malignant focus then can be located with highest accuracy. PET and PET/CT has been found to be useful in, for example, CNS tumors, lymphomas, soft-tissue tumors, neuroblastoma, malignant bone tumors and germ cell tumors. PET/CT has a limited role in early diagnosis, however, it plays an important role in initial staging, treatment response evaluation and detection of metastatic disease in these cancers. Despite the fact that PET/CT has better diagnostic value when compared with conventional imaging, such as CT and MRI, in the management of many pediatric cancers, there are certain limitations. PET/CT has a limited role in detection of lesions smaller than 5 mm, well-differentiated tumors and tumors with low metabolic rate. Many infections and inflammation can lead to false-positive PET/CT results. In the present review we will discuss the various clinical indications of PET and PET/CT in pediatric cancers.